Electrochemistry and in-situ spectroelectrochemistry properties of N-, S-substituted-1,4-naphthoquinone compounds (NQ's) - KOCA, ATIF (My University, 2023)
Quinones are ubiquitous in nature and form one of the largest classes of antitumor agents approved for clinical use. Naphthoquinones and their derivatives are important in many fields such as pharmaceutical, medical, and environmental applications. It is also known that such compounds show strong biological activity against various bacteria, viruses, fungi, and cancer cells. They are known to be efficient in inhibiting cancer cell growth. Under physiological conditions, they can undergo non-enzymatic one-electron reduction to give the moderately toxic species of semiquinone radical-anion. Thus, the electrochemical study of quinones might provide a basic knowledge of semi-quinone radical formation in both in vivo and in vitro under different media. In this study, firstly, novel N-, S- and/or halo(Br/Cl)-substituted-1,4-naphthoquinone derivatives (2a-d, 3e, 4, 6a-f, 7, 8 and 9) were synthesized. The structures of all compounds were elucidated by using spectroscopic methods [FT-IR, NMR (1H/13C), MS, and microanalysis]. Electrochemical characterization indicated that all compounds underwent two well-resolved reduction reactions assigned to NQ/NQ.− and NQ.−/NQ2− processes respectively. Additionally, an all-defined irreversible oxidation wave was also recorded for all compounds. The substituents on the NQ ring altered the peak position and reversibility of the electron transfer reactions. Redox processes considerably influenced the spectra of the compounds which showed different colors and spectra for different electrogenerated anionic and cationic forms of the compounds.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Analitik Kimya; Fizikokimya; Elektrokimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Analytical Chemistry; Physical Chemistry; Electrochemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, KİMYASAL; KİMYA, ANALİTİK; ELEKTROKİMYA; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; ENGINEERING, CHEMICAL; CHEMISTRY, ANALYTICAL; ELECTROCHEMISTRY; Fizik Bilimleri; Genel Kimya Mühendisliği; Physical Sciences; General Chemical Engineering; Cyclic Voltammetry; In situ UV–Vis spectroelectrochemistry; NMR Spectroscopy; Quinones